z+12=4z-7

Simple and best practice solution for z+12=4z-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z+12=4z-7 equation:


Simplifying
z + 12 = 4z + -7

Reorder the terms:
12 + z = 4z + -7

Reorder the terms:
12 + z = -7 + 4z

Solving
12 + z = -7 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
12 + z + -4z = -7 + 4z + -4z

Combine like terms: z + -4z = -3z
12 + -3z = -7 + 4z + -4z

Combine like terms: 4z + -4z = 0
12 + -3z = -7 + 0
12 + -3z = -7

Add '-12' to each side of the equation.
12 + -12 + -3z = -7 + -12

Combine like terms: 12 + -12 = 0
0 + -3z = -7 + -12
-3z = -7 + -12

Combine like terms: -7 + -12 = -19
-3z = -19

Divide each side by '-3'.
z = 6.333333333

Simplifying
z = 6.333333333

See similar equations:

| 90+90+(2x-4)+(3x-29)=360 | | 45x-9y=18 | | -9=3x+5 | | 4x^2+45=20x | | 848/0 | | w(w-6)=0 | | 8t+2(1-5t)= | | 4x^2+28x=-61 | | -3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11 | | 2/5=x/25 | | 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) | | -1(3x+4)-4x=-2(4x-3)+2 | | 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k | | 2x^8-4x^7+10x^6=0 | | x/48=6/12 | | 3x+3(x+2)=6 | | 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 |

Equations solver categories